Comparison of the effects of static and dynamic stretching on the force-velocity capabilities of young volleyball players - Popelka, J.; Pivovarnicek, P. (Journal of Physical Education and Sport, 2018)
The aim of the study was to compare the effects of static (StatS) and dynamic stretching (DynS) on forcevelocity tasks (spike jump - SJ, block jump - BJ, 1 kg ball throw - THW) of young volleyball players (n = 10, age = 15.4±0.5 years, height = 177.5±4.7 cm, weight = 61.0±5.7 kg) during their competition period. The statistical analysis did not show any significant differences (t = -0.074, p > 0.05, d = 0.02) when measuring the SJ height after the StatS warm-up (58.3±10.0 cm) and after the DynS warm-up (58.9±10.1 cm). No significant differences were observed with the BS height (t = -0.214, p > 0.05, d = 0.05) - StatS warm-up (42.3±9.2 cm) and DynS warm-up (43.1±9.3 cm). The THW indicator came up similar (t = 0.164, p > 0.05, d = 0.04), StatS warmup 12.2±3.2 cm, DynS warm-up 13.0±2.9 cm.